PENGOBATAN TRADISIONAL PATAH TULANG DI DESA SIMALINYANG KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR - Rili Monica; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The research was conducted in Simalinyang village, Kampar Distric. The purpose of this study is to know the knowledge of people/patients about diseases and to know knowing the background of the people choose to come to traditional treatment of fractures. The focus topic of this research is knowing the community/patient knowledge about the disease. The samples in this study amounted to 5 people. The authors use qualitative methods and use the Accidental Sampling retrieval technique. Data instruments are observations, interviews and documentation. From the research conducted, the authors found that all research subjects or people in Simalinyang village generally know well the conformity of bone fractures with drugs used by herbalists. Research finds that not all research subjects or communities know the types of fractures experienced. From research conducted, only one person of research subject knows about the types of fractures. Researchers found that all research subjects gained healing from traditional medicine in approximately three months.  The traditional treatment of fractures carried out research subjects, the cost of treatment is set based on the type of fractures. In addition, patients can treat the cost of treatment. The patient has an emotional attitude with the shamans who treat it. That is, from hereditary family of patients already have treatment in bone fractures. Therefore, the research subject considers to follow the drug habit. Keywords: traditional medicine, Sociology of health